Pengaruh Employee Engagement dan Kepuasan Kerja terhadap Turnover intention Tenaga Pendidik di Yayasan Huffadhlul Qur’an Jauharotul’arifin - Maulana Ihsan Mausuf; Raisa Hilia Aini Syifa (Universitas Kristen Indonesia Toraja, 2026)
This research is motivated by the phenomenon of a high teacher turnover rate at a non-profit religious education institution, which potentially disrupts curriculum continuity and the quality of students' Quranic memorization. This study aims to analyze the partial effects of employee engagement (X1) and job satisfaction (X2) on the turnover intention (Y) of teaching staff. A quantitative associative approach with a survey method was employed. The population consisted of all 52 teachers at the Huffadhul Qur’an Jauharotul’Arifin Foundation. The sampling technique used was saturated sampling (census), whereby the entire population was designated as respondents. Data collection instruments utilized structured questionnaires with a 1-5 Likert Scale distributed directly. Data analysis techniques included classical assumption tests, multiple linear regression analysis, coefficient of determination (R2), and partial hypothesis testing via t-test using SPSS software. The results indicated that partially, employee engagement has a significant negative effect on turnover intention. Similarly, job satisfaction was proven to have a significant negative impact on turnover intention. The coefficient of determination value demonstrates that both independent variables contribute substantially to explaining the variance in teachers' intention to quit. The practical implications of this research emphasize the importance of foundation management in maintaining organizational stability by strengthening emotional alignment (Quranic vision) and fostering a conducive, harmonious working environment while providing fair appreciation toward the teaching profession.